Pseudo Identity in Cassava Rice as A Traditional Religious Identity Struggle Against Contemporary Religious Discrimination - Ardiansyah, Anton; Sihabudin, Ahmad; Dua, Mikhael (Indonesian Journal of Social Science Research, 2024)
The people of Cireundeu Village are known as a community group that still maintains the tradition of ancestral heritage of consuming rasi (cassava rice) as a staple food since 1918. This consumption process imbues rasi with the meaning that it is part of their culture. This study employed a qualitative approach with a semiotic method in decoding the meaning of rasi among the people of Cireundeu indigenous village. The purpose of this study was to find out 1) what meaning is constructed from rasi as their staple food 2) and what identity is built among the Cireundeu indigenous people. The results of this study show that 1) rasi is a form of struggle for religious identity that has been discriminated against, namely the struggle for belief in Sunda Wiwitan as their religious identity and 2) rasi as a group identity is a pseudo-identity of the Cireundeu indigenous people who primarily exist to maintain group beliefs in their beliefs.